Contribution of Hepatitis C Infection to a Large Cohort of Cryoglobulin-Positive Patients: Detection and Characteristics - Kolopp-Sarda, Marie N.; Miossec, Pierre (Frontiers in Immunology, 2020)
Cryoglobulins (CG) are cold precipitating immunoglobulins, and HCV infection is its most common cause. The purpose of the study was to determine the contribution of HCV in a large cohort of CG. Biological characteristics and specificity of CG in HCV patients were compared to non-HCV subjects. CG analysis included isotype, clonality, concentration and rheumatoid factor (RF) in cryoprecipitate; and serum complement and RF. This study is an extension of a previous study carried out on a cohort of samples of 3,439 patients tested for CG from all medical units, in which 1,675/13,439 (12.5%) patients had a CG and 680/1,675 (40.6%) had HCV serology or viral load (VL) determination. Among these 680 CG patients tested for HCV, 325/680 (47.8%) HCV patients (272 HCV VL+ and 45 HCV VL- patients) were compared to 355/680 (52.2%) non-HCV subjects. After a positive detection of CG, HCV status was determined only for 37.7% (256/680) patients, allowing the diagnosis of a previously unknown HCV infection for 39.8% (102/256). Concentration of HCV VL+CG (median 80.5 mg/liter) was significantly higher than HCV VL-CG (median 50.5 mg/liter, p=0.001) and HCV- CG (median 32 mg/liter, p<0.0001). There was no difference of median CG concentration between HCV VL- patients and non-HCV subjects. RF titer was significantly higher in type II CG compared to type III CG in HCV VL+ patients (254±720 versus 15±21 IU/ml, p<0.0001) and non-HCV subjects (333±968 IU/ml versus 16.8±26 IU/ml, p=0.0004). Complement functional activity CH50 was lower in HCV VL+ patients (36±24 units/ml) and in HCV VL- patients (32±21 units/ml) than in non-HCV subjects (50±25 units/ml, p=0.001 and p=0.004). In conclusion, HCV infection and treatment influence CG characteristics. It is essential, and far from always tested, to determine the HCV status of patients with mixed CG, and conversely to search for CG in patients with HCV infection.